Buzz Aldrin: Mission to Mars. (November 2014) - Leach, Neil
<x xml:space="preserve">Abstract</x> The lunar landings in 1969 provided the watershed moment for space exploration, bringing the celestial into direct physical contact with man for the first time. As the second man to walk on the Moon, Buzz Aldrin maintains a unique place in American and space history. Here, Guest‐Editor Neil Leach looks at why Aldrin has chosen to highlight the potential of Mars over the Moon in his recent book, Mission to Mars: My Vision for Space Exploration (2013).